APTITUDE AEROBICS IN APPRENTICES OF WALK THAT ACCOMPLISH SOLEMNITY PRESCRIPTION OF THE EXERCISE (Fiep Bulletin - online, 2015)
Objective: In order to characterize the profile of the aerobic aptitude in walk apprentices who accomplish exercise solemnity prescription. Method: It is a traverse study, accomplished with n=42, of the feminine gender, age group from 23 to 56 years, they were divided in age groups. The data were obtained through handbook of personal data, data collection record and in the application of the Mile Test (Kline, 1987). The analysis was made through descriptive statistics, using the percentage, average and standard deviation of the indicators. Results: The practice of the walk is defined as the exercise type, and it is defined for the research bound itself; as to the weekly frequency, all the age groups present an average non inferior to 4 weekly sessions; considering the duration of the session, the lowest average found among the groups it was 57 minutes for session. There was not parameter for measure the intensity, which could be considered as a comfort state in the accomplishment of the exercise. It is probable that the intensity is the decisive factor in the cases of risk condition and low aptitude aerobics found in the test. As to the aerobic conditioning, most of the apprentices of the 3 younger groups are in the advisable strip of aptitude aerobics. The group from 50 to 59 years has most of their apprentices in risk condition. In all the groups there are apprentices in athletic condition. Above the 30 years cases of risk condition appear and the aptitude is decreased, according to data presented on Table 1. In such cases, the apprentices seem not exercise enough to acquire the benefits of the physical activity, turning evident the correction needing and adaptation of the exercise prescription.Conclusion: In spite most of the apprentices present a satisfactory condition of aptitude aerobics, the orientations and the professional accompaniment are recommended in all the ages. A larger attention seems to be indispensable starting from the 30 years, being this, the age group where cases of aptitude aerobics appear below the advisable strip for the health, possibly caused by the solemnity prescription of exercises. Probably, an increment of the intensity is enough to alter this picture of aptitude aerobics indicators, improving the apprentices' conditioning.
Keywords: Physical Activity; Aerobic Aptitude; Exercise Prescription.